Tensile Strength Study of Composite Materials Reinforced with Durian Fiber and Recycled Plastic Using Compression Molding Method - Isra, Muhammad; Fauzan; Muhammad Nuzan Rizki; Tjut Rizqi Maysyarah Hadi; Akbar Rizqullah (Malikussaleh Journal of Mechanical Science and Technology, 2025)
Efforts to manage waste are being carried out at various levels, ranging from households to large-scale industries that generate waste on a daily basis. The imbalance between waste generation and proper management has turned waste into a serious environmental concern. Among the different types of waste, plastic is one of the most difficult to naturally decompose (non-biodegradable) and represents the largest portion compared to other waste materials. Statistical data show that in several cities across Indonesia, the amount of non-biodegradable waste disposed of at final disposal sites reaches 6,598.23 tons per day. This study was conducted with both general and specific objectives. The general aim was to utilize plastic waste as a composite material, while the specific objective was to analyze the tensile strength properties of composites produced from plastic waste reinforced with durian fibers. By exploring the potential of plastic waste in construction materials, this research seeks to provide a sustainable solution to the plastic waste problem while contributing to environmental preservation. Four different specimens were prepared for testing: Specimen A (80% plastic waste and 20% durian fiber), Specimen B (60% plastic waste and 40% durian fiber), Specimen C (40% plastic waste and 60% durian fiber), and Specimen D (20% plastic waste and 80% durian fiber). The results revealed that Specimen B exhibited the highest average tensile strength of 20.9 MPa, indicating significant potential for enhancing material performance. In contrast, Specimen D showed the lowest average tensile strength of only 1.2 MPa, highlighting the need for further composition optimization to improve mechanical properties. Overall, this study provides valuable insights into the development of recycled composite materials for use in construction and broader industrial applications.